A NEW COMBINATION AND A NEW NAME IN GYNOCHTHODES (RUBIACEAE) - K. M. WONG; SYLVAIN G. RAZAFIMANDIMBISON (Research Center for Biology, 2015)
WONG, K. M. & RAZAFIMANDIMBISON, S. G. 2015. A new combination and a new name in Gynochthodes (Rubiaceae). Reinwardtia14(2): 297 - 298. - The new combination Gynochthodes lanuginosa (Suratman) K. M. Wong & Razafim. and the new name Gynochthodes suratmanii K. M. Wong & Razafim., the latter in place of Morinda wongiana Suratman, are proposed.